Carica Papaya leaf-infused metal oxide nanocomposite: a green approach towards water treatment and antibacterial applications - Rangayasami Aswini (22047767) (2024)
This study successfully synthesized ZnO–CuO nanocomposite using the hydrothermal method with Carica papaya leaf extract. The incorporation of the leaf extract significantly enhanced the nanocomposite properties, a novel approach in scientific research. Characterization techniques, including X-ray diffraction, Fourier Transmission Infrared spectroscopy, and Scanning Electron Microscopy with Energy Dispersive X-Ray Analysis, confirmed a cubic crystal structure with an average size of 22.37 nm. The Fourier Transmission Infrared spectrum revealed distinctive vibrations at 627, 661, and 751 cm−1 corresponding to ZnO–CuO nanocomposite corresponding to stretching and vibration modes. SEM images confirmed a cubic-like and irregular structure. The nanocomposite exhibited outstanding photocatalytic activity, degrading methylene blue dye by 96.73% within 120 min under visible light. Additionally, they showed significant antimicrobial activity, inhibiting Staphylococcus aureus (20 mm) and Klebsiella pneumonia (17 mm). The results highlight the efficiency of Carica papaya leaf-derived ZnO–CuO nanocomposite for environmental and health challenges. Other Information Published in: Environmental Geochemistry and Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10653-024-02090-4